Biochemical Characterization of Cellulase From Bacillus subtilis Strain and its Effect on Digestibility and Structural Modifications of Lignocellulose Rich Biomass - Malik, Waseem Ayoub; Javed, Saleem (Frontiers in Bioengineering and Biotechnology, 2021)
Microbial cellulases have become the mainstream biocatalysts due to their complex nature and widespread industrial applications. The present study reports the partial purification and characterization of cellulase from Bacillus subtilis CD001 and its application in biomass saccharification. Out of four different substrates, carboxymethyl cellulose, when amended as fermentation substrate, induced the highest cellulase production from B. subtilis CD001. The optimum activity of CMCase, FPase, and amylase was 2.4 U/mL, 1.5 U/mL, and 1.45 U/mL, respectively. The enzyme was partially purified by (NH4)2SO4 precipitation and sequenced through LC-MS/MS. The cellulase was found to be approximately 55 kDa by SDS-PAGE and capable of hydrolyzing cellulose, as confirmed by zymogram analysis. The enzyme was assigned an accession number AOR98335.1 and displayed 46% sequence homology with 14 peptide-spectrum matches having 12 unique peptide sequences. Characterization of the enzyme revealed it to be an acidothermophilic cellulase, having an optimum activity at pH 5 and a temperature of 60 °C. Kinetic analysis of partially purified enzyme showed the Km and Vmax values of 0.996 mM and 1.647 U/mL, respectively. The enzyme activity was accelerated by ZnSO4, MnSO4, and MgSO4, whereas inhibited significantly by EDTA and moderately by β-mercaptoethanol and urea. Further, characterization of the enzyme saccharified sugarcane bagasse, wheat straw, and filter paper by SEM, ATR-FTIR, and XRD revealed efficient hydrolysis and structural modifications of cellulosic materials, indicating the potential industrial application of the B. subtilis CD001 cellulase. The findings demonstrated the potential suitability of cellulase from B.subtilis CD001 for use in current mainstream biomass conversion into fuels and other industrial processes.